Optical coherence tomography angiography in retinitis pigmentosa: A narrative review. Issue 34 (26th August 2022) - Lu, Bingwen; Chao, Guojun; Xie, Like
Abstract : Retinitis pigmentosa (RP) is a group of inherited retinal disorders characterized by progressive rod and cone photoreceptor degeneration. Changes in retinal vasculature have long been associated with RP. Optical coherence tomography angiography (OCTA) is a novel imaging technology that enables noninvasive visualization of the retinal and choroidal microvasculature. OCTA enables quantification of microvascular changes in the retinal capillary plexus and choriocapillaris, in addition to qualitative feature description. Therefore, OCTA has the potential to become an important tool for better understanding, early detection, progression, and treatment of RP. In this review, we focus on the applications of OCTA in clinical research on RP. We also discuss future improvements in the OCTA technology for RP management. We believe that the advancement of the OCTA technique will ultimately lead to a better understanding of RP and aid in the prevention of visual impairment.